Al-Qurán Dan Wahyu : Suatu Tinjauan Terminologis - Agustiar Abbas; Hasan Basri; Sri Wulan Dari; Tama Erlanda Putri; Parisyi Algusyairi; Nurhayuni Nurhayuni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Islam is based on the Al-Qur'an which regulates all aspects of Muslim life. Terminology related to the Qur'an and revelation with the aim of providing treasures. By understanding this terminology, it is hoped that we can better apply Islamic teachings in our daily lives and increase our understanding of Islamic teachings as a whole. The aim in compiling this work is to understand and describe and analyze the Al-Qur'an and Revelation: an overview of terminological aspects. Qualitative descriptive research in this work is to provide a detailed explanation of the characteristics, phenomena, or circumstances of an object of research. Literature research or literature search has a broader function than just to obtain data in a study. The results of this work are 1). As a divine revelation, it provides comprehensive guidelines and rules for human life to achieve true life goals. 2). As the main source of law in the Islamic religion that regulates human behavior and teaches the importance of maintaining the purity of the heart and implementing the principles of Shari'a. 3). As a warning, conditioning, and an important source of teachings for Muslims. 4). Teach that Allah has the attribute of mercy that encompasses the entire universe and His creatures. And 5). As a complement and closing of the previous teachings.